2017
DOI: 10.1128/jb.00871-16
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic and Mutant Analysis of the CO 2 Concentrating Mechanism of Hydrothermal Vent Chemolithoautotroph Thiomicrospira crunogena

Abstract: Many autotrophic microorganisms are likely to adapt to scarcity in dissolved inorganic carbon (DIC; CO 2 ϩ HCO 3 Ϫ ϩ CO 3 2Ϫ ) with CO 2 concentrating mechanisms (CCM) that actively transport DIC across the cell membrane to facilitate carbon fixation. Surprisingly, DIC transport has been well studied among cyanobacteria and microalgae only. The deep-sea vent gammaproteobacterial chemolithoautotroph Thiomicrospira crunogena has a low-DIC inducible CCM, though the mechanism for uptake is unclear, as homologs to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 61 publications
0
23
0
Order By: Relevance
“…Previous studies suggested that in some proteobacterial species, cytosolic form IAq RuBisCOs exhibit a higher affinity and specificity for CO 2 even in the presence of O 2 [53]. During periods of high dissolved inorganic carbon (DIC) and NH 3 -limited conditions, cells favor upregulated production of the cytosolic form RuBisCO because of its higher sensitivity to fluctuating inorganic carbon concentrations compared to the carboxysomal counterpart [54].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies suggested that in some proteobacterial species, cytosolic form IAq RuBisCOs exhibit a higher affinity and specificity for CO 2 even in the presence of O 2 [53]. During periods of high dissolved inorganic carbon (DIC) and NH 3 -limited conditions, cells favor upregulated production of the cytosolic form RuBisCO because of its higher sensitivity to fluctuating inorganic carbon concentrations compared to the carboxysomal counterpart [54].…”
Section: Discussionmentioning
confidence: 99%
“…Under low-DIC conditions, all genes assayed here encoding members of two distinct clusters within the SbtA family, and two clusters of homologs of the Tcr_0853-and Tcr_0854-encoded transporter from H. crunogenus (17), were upregulated, whether adjacent to carboxysome loci or not (Table 2). When genes encoding members of the Chr and SulP families were adjacent to carboxysome loci, they were also upregulated under low-DIC conditions (Table 2).…”
Section: Resultsmentioning
confidence: 98%
“…To determine whether carboxysome-associated transporter gene transcripts were more abundant when cells were grown under low-DIC conditions, taxa that were amenable to cultivation in chemostats were grown under two conditions: DIC limitation (low-DIC condition) and NH 3 limitation (high-DIC condition) (14). Cells were harvested via centrifugation (10,000 ϫ g, 5 min, 4°C), flash-frozen with liquid nitrogen, and stored at -80°C for subsequent RNA extraction using the Ambion RiboPure-Bacteria kit (17). Primers were designed to target genes encoding carboxysome components (csoS2; csoS3; positive control for CCM induction), citrate synthase (calibrator for the 2 -ΔΔCT method) (47), and transporters (Table 4), and qRT-PCR assays were implemented in an Applied Biosystems Step One real-time PCR system, using QuantiTect SYBR green RT-PCR (Qiagen, Inc.) as described in reference 17.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations